Economic De-Growth: A Theoretical and Critical Review (Global Journal of Human-Social Science, 2021)
The aim of this article is to present a bibliographical review on the theme of de-growth, firstly discussing the emergence, the main foundations and the proposals of this theoretical conception. Subsequently, the most relevant critical arguments to this approach are exposed, both in relation to its internal consistency and the possibility of a de-growth program being compatible with a capitalist economy. The result of this review points to the need to advance in the construction of a more robust theoretical formulation on de-growth, considering the main criticisms presented in recent years.